Statistical research of the factors which affect the acceptance of advanced driving assistance system among youngsters - Ting Tin Tin; Yap Eurig; Yeong Eugene; Kong Jun Wei; Tan Khai Xiun; Wan Nor Al-Ashekin Wan Husin; Ali Aitizaz; Lee Kuok Tiung; Ayodeji Olalekan Salau; Umar Farooq Khattak; Yasin Ahmed Siddiqui (Scopus, 2024)
The automotive industry has witnessed significant growth over the course of over a century since the inception of the first car and so has the frequency of car accidents. The Advanced Driver Assistance System (ADAS) has emerged as a significant invention in aiding drivers in preventing accidents. This technology is gradually being integrated into newly built automobiles. This study examined and developed a model for the acceptance of ADAS systems among young people in TARUMT, considering external factors, based on the literature review and technology acceptance extension models such as TAM and UTAUT. Additional elements that will influence the acceptance of the ADAS system among young individuals are also considered. To verify the model, we employ PSPP to determine the Pearson's Correlation for each element. This study reveals that various factors, including Social Norm, Trust rank, enjoyment, attitude, and Perceived Usefulness, exhibit a significant correlation with Behavioral Intention. Additionally, Perceived Ease of Use, Perceived Usefulness, Safety Risk, Privacy Risk, Individual Innovation, Environmental Protection, and Symbolic Value demonstrate a significant correlation with Attitude. Furthermore, Reliability exerts significant influence on Perceived Usefulness, Enjoyment is significantly related to Perceived Ease of Use, and Perceived Ease of Use exhibits significant correlation with Perceived Usefulness. We employed an online questionnaire developed using Google Form for data collection and distributed a link to friends who are also studying at TARUMT. 162 sets of answers was gathered. The proposed model offers enhanced survey models and assistance to car manufacturers in gaining insights into the acceptance of Advanced Driver Assistance Systems (ADAS) among young individuals in TARUMT. This information can be utilised to determine areas for improvement in the research and development of ADAS systems. Additionally, it can serve as a valuable reference for the government in formulating more effective policies pertaining to ADAS systems.